Preface of Special Issue No. 7 - Heard, Doug; Williams (issue eds.), Mark (Rangifer, 1991)
There is a close association between caribou and people in the Northwest Territories. The workshop logo depicted that relationship and maintained our awareness of that fact throughout the workshop. We were happy to see that the public and interested groups from in and around Yellowknife took advantage of the opportunity to learn more about caribou biology and management. The entire second year class of the Renewable Resource Training Program from the Thebacha Campus of Arctic College in Fort Smith attended and both the Denendeh Conservation Board and the Beverly and Kaminuriak Caribou Management Board scheduled meetings in Yellowknife to correspond with this workshop.